DEVELOPMENT OF THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM CONSIDERING ACADEMIC AND PRACTICAL BALANCE - Sarwo Edy; Sumarta; Arifin, Bambang Samsul (Journal of Language and Literature Education, 2024)
This study investigates the development of the Islamic Religious Education (PAI) curriculum with a focus on achieving a balance between academic and practical components. The primary objective is to create a curriculum model that integrates theoretical knowledge with practical applications, thereby fostering a comprehensive understanding and real-world skills among students. The research methodology includes qualitative analysis through interviews and observations, providing insights into the strengths and weaknesses of the current PAI curriculum. Key findings suggest that an effective implementation of a balanced curriculum requires meticulous planning, continuous professional development for educators, sufficient resources, and ongoing evaluation. The proposed curriculum model encompasses essential elements such as detailed theoretical instruction, interactive practical activities, and regular assessments to ensure both relevance and efficacy. Furthermore, strategies for successful implementation are highlighted, including stakeholder involvement, structured training programs, and systematic resource allocation. The study's contribution lies in its practical recommendations for educators and policymakers, aimed at enhancing the quality of Islamic Religious Education. By addressing the identified challenges and providing actionable strategies, this research supports the development of a more balanced and effective PAI curriculum, ultimately benefiting the holistic development of students and the educational system as a whole.